Use of High-rise Apartments as an Urban Densification Policy: Lessons from China, Egypt and Ethiopian Condominiums - Rimai , Kudzai; Hickonicko, Beatrice; Mudehwe, Raymond (Lighthouse: The Zimbabwe Ezekiel Guti University Journal of Law, Economics and Public Policy, 2025)
The article is based on a study that discussed the use of high-rise apartments as an urban densification policy, drawing lessons from China, Egypt and Ethiopia. Urban growth has seen the sprawling of cities along with the new demands for housing due to population growth. Cities continue to have housing backlogs as people continue to have improved life expectancies around the world. The problem in the study is the affordability and accessibility challenges created by high-rising apartments due to the liberalisation of land development policies. The research uses a qualitative research methodology with a bias towards the case study research design. The study employed secondary information as the data collection method using Google Scholar articles. The research used thematic data analysis. The study findings reveal that densification can create solutions to urban sprawl, while unaffordability issues can arise for low-income earners. The findings also indicate that densification can suffer from the commodification of housing which can lead to housing backlogs of low-income earners. The study concludes that privatisation of land development makes densification a time bomb waiting to blow in the face of low-income earners. It recommends the nationalisation of housing projects to improve accessibility and affordability of housing for low-income earners.